2017
DOI: 10.1007/s10897-017-0084-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Prenatal Genetic Counseling, Prenatal Genetic Testing, and Termination of Pregnancy among Southeast and East Asian Women in the United States

Abstract: Recognizing the heterogeneity of the Asian population with regards to acculturation, education, health awareness, and cultural values is vital for tailoring culturally sensitive and appropriate care. Prior studies show that cultural values influence perceptions of genetics within Asian populations. The reputation of the family unit factors into decisions such as pregnancy termination and disclosure of family medical history, and the nondirective model of American genetic counseling may conflict with the histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
5
16
1
Order By: Relevance
“…Of note, subjective norms related to professionals, which comprised of physicians and other health professions (e.g., nurses, social workers, psychologists, and occupational/physical/speech therapists), were found to be significantly and positively associated with participating mothers' attitudes toward PGT for detecting ASD susceptibility genes. This result is consistent with past studies, which suggested that individuals' attitudes toward genetic testing were influenced by health professionals [32,50,52]. Yet, it is important to highlight that the attitudes of the school teachers of the children with ASD could also affect mothers' attitudes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of note, subjective norms related to professionals, which comprised of physicians and other health professions (e.g., nurses, social workers, psychologists, and occupational/physical/speech therapists), were found to be significantly and positively associated with participating mothers' attitudes toward PGT for detecting ASD susceptibility genes. This result is consistent with past studies, which suggested that individuals' attitudes toward genetic testing were influenced by health professionals [32,50,52]. Yet, it is important to highlight that the attitudes of the school teachers of the children with ASD could also affect mothers' attitudes.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in our previous qualitative study, abortion is the most prominent motivation for Taiwanese parents of children with ASD to undergo PGT for detecting ASD susceptibility genes. The potential explanation could be that in Taiwan, having a child with mental, intellectual, or development disability is associated with cultural stigma and disgrace for the family, which may impact mothers' perceptions regarding PGT and abortion [13,50]. Moreover, the Genetic Health Act [51] in Taiwan has made abortion easier for pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for a unique population with limited experience in genetics and healthcare, a nondirective approach can have potential drawbacks as nondirectiveness may contradict the population's cultural expectation in health care. Patient confusion and frustration, resistance behaviors, and inappropriate decision‐making are drawbacks previously reported in other ethnic populations (Tsai et al, ; Wang & Marsh, ; Wessels, Koole, & Penn, ). It can also lead to a perception of providers not being knowledgeable, as shown by our results.…”
Section: Discussionmentioning
confidence: 81%
“…These variables seem to be available in Asian populations, even in the members of families which immigrated to other countries. [9] A physician offering genetic consultation should take all these characteristics in consideration. It is clear that this procedure, which is a kind of psychotherapy session, should be carried out in an unbiased and non-directive manner.…”
Section: Discussionmentioning
confidence: 99%